Dimensional Stability Test of Mahogany Wood by Heat Treatment - Kusumawardhani, Dina Tiara (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2024)
Mahogany wood (Swietenia macrophylla) is one of Indonesia's fast-growing commercial tree species. Its wood is widely used for construction because of its great potential in the timber industry. Mahogany wood has low dimensional stability and high hygroscopic properties. This study aims to improve the quality of mahogany wood in terms of dimensional stability with the heat treatment method. Samples of mahogany wood were heat treated with three-time levels, namely control, 3 hours, and 6 hours at 180 °C. The results showed that heat treatment at 180 °C for 6 hours had the best results for maintaining wood dimensions with a low increase in water content, increased specific gravity, low absorption ability, minor swelling of wood in three directions of wood, and the value of ASE is also common than 3 hours of treatment.